Энергетический мониторинг пищевых технологий - Бурдо, О. Г.; Семков, С. В.; Сталимбовская, А. С. (НТУ "ХПИ", 2007)
The analysis of power problems in the world, Ukraine, in agrarian and industrial complex is given. Specificity of power technologies of agrarian and industrial complex is determined. Strategy of the decision of questions of power efficiency in agrarian and industrial complex is offered. The operational experience of academy on problems of increase of efficiency of use of resources in food technologies is resulted.
Keywords: ресурсосбережение; энергопотребление; энергосбережение; энергетическая политика Украины; энергоэффективность; расход топлива